Sosialisasi Pentingnya Air Kaya Hidrogen (AKH) untuk Kesehatan Tubuh di Desa Persil, Kecamatan Batukliang Utara, Kabupaten Lombok Tengah, Nusa Tenggara Barat - Musparlin Halid; Adriyan Suhada; Hardani; Beny Binarto Budi Susilo; Yan Reiza Permana; Alfisahrin (AL HAYAT: Jurnal Pengabdian Masyarakat, 2024)
One form of activity in health promotion is in the form of socialization that we do. These activities strengthen the skills and abilities of individuals to take action, and the capacity of groups or communities to act collectively to exercise control over the determinants of health. Socialization activities strengthen the skills and abilities of individuals to take action, and the capacity of groups or communities to act collectively to exercise control over the determinants of health. This activity uses lecture, discussion and question and answer methods with residents. The location of the activity was Persil Village, Central Lombok with 25 participants and accompanied by 3 lecturers and 5 students. The results of our socialization show that local residents need solutions to health problems and hope that Hydrogen Rich Water (AKH) is a solution to the disease problems that they and their families are currently facing. The knowledge of the local community is still categorized as low and requires special attention from the local government and stakeholders. Some residents who participated in the activity had a history of their own diseases, such as gastritis, cholesterol, high blood pressure, allergies and some of their families also had a history of certain diseases, such as kidney stones, diabetes, stroke, cancer and so on. Persil villagers gained knowledge about health, especially the differences in various kinds of water consumed daily. The villagers originally thought that all water is the same, but after we provided information about water, the villagers became more understanding and more selective about the drinks they consume daily.